Alternative Development Narratives, Policies and Outcomes in the Andean Region - Humberto Campodónico; Gilles Carbonnier; Sergio Tezanos Vázquez (Revue Internationale de Politique de Développement)
Since the early 2000s, many Latin American countries achieved remarkable economic growth coupled with poverty and inequality reduction, largely due to the pursuit of a centuries-old pattern of commodity exports. The end of the commodity price super-cycle in 2014 puts some of these development gains in jeopardy, raising anxiety among emerging middle classes wary of slipping back into poverty. Drawing on a rich intellectual heritage, Latin American leaders have designed novel approaches in the pursuit of sustainable development. Alternative development narratives brought to the fore by left-wing governments have emphasised notions such as buen vivir1, arguably the most influential and revolutionary proposition originated in the region since different variants of the dependency theory. What is less clear is the extent to which competing ideologies and narratives have translated into diverging outcomes, be it with regard to (neo-) extractivism, ecological sustainability or the rights and cultural identity of indigenous peoples, or simply in terms of economic diversification. This chapter introduces the thematic issue of International Development Policy, which deals with recent paradigmatic innovations and development experiences in Latin America, with a particular focus on the Andean region.